Ablation Reboots the Response in Advanced Hepatocellular Carcinoma With Stable or Atypical Response During PD-1 Therapy: A Proof-of-Concept Study - Lyu, Ning; Kong, Yanan; Li, Xiaoxian; Mu, Luwen; Deng, Haijing; Chen, Huiming; He, Meng; Lai, Jinfa; Li, Jibin; Tang, Hailin; Lin, Youen; Zhao, Ming (Frontiers in Oncology, 2020)
Background: The anti-programmed cell death protein-1 (PD-1) inhibitor is one of the second-line therapies for advanced hepatocellular carcinoma (HCC) after sorafenib failure. The goal of this study is to evaluate the feasibility and safety of ablation on the tumour in patients with advanced HCC who had stable disease or atypical response during single anti-PD-1 therapy after sorafenib failure. Atypical response defined as mixed responses in different lesions of the same individual (e.g., active or stable lesions mixed with progressive lesions). Patients and Methods: This proof-of-concept clinical trial enrolled 50 patients treated with an anti-PD-1 inhibitor of nivolumab or pembrolizumab monotherapy between July 2015 and Nov 2017. Thirty-three cases with stable disease or atypical response to anti-PD-1 inhibitor received subtotal thermal ablation. The safety and the response of ablation during anti-PD-1 therapy were evaluated. The survival was estimated by the Kaplan-Meier curve. Results: Of all 50 patients treated with anti-PD-1 therapy, the rate of response, stable disease, atypical and typical progression were 10% (n=5), 42% (n=21) 32% (n=16) and 12% (n=6), respectively. Additional ablation improved efficacy with tolerable toxicity, and the response rate was increased from 10% to 24% (12/50). The median time to progression, progression-free survival, and overall survival was 6.1 months (95%CI, 2.6-11.2), 5 months (95%CI, 2.9-7.1) and 16.9 months (95%CI, 7.7-26.1), respectively. Conclusions: This proof-of-concept trial suggested that additional ablation may increase the objective response rate with tolerated toxicity and achieved a relatively better median survival, in advanced HCC patients who had stable or atypical progressive diseases during anti-PD-1 therapy, which may provide a potentially promising strategy to treat advanced HCC. (ClinicalTrials.gov identifier: NCT03939975)